KEDUDUKAN HUKUM PIDANA ADAT DALAM HUKUM PIDANA INDONESIA - Kusyandi, Adi; Salsabila, Sahda; Murtiningsih, Murtiningsih (Yustitia, 2023)
The development of Indonesian law is heading in a positive direction as evidence that law in Indonesia is a dynamic law, in the dynamism of Indonesian law, one form is Law Number 1 of 2023 concerning the Criminal Code, in which the Republic of Indonesia drafts provisions of Indonesian criminal law by using Indonesian culture and local wisdom as a spirit or soul in Indonesian law itself. Local wisdom is a local idea (local) that is wise, full of wisdom, good value, which is embedded and followed by community members. So that between the construction of national law and the concept of local wisdom is able to go together, legal harmonization becomes very important in the preparation and formulation of the contents in the New Penal Code Law, Article 66 paragraph (1) letter f which states that, Additional crimes as referred to in Article 64 point b consist of: f. fulfillment of local customary obligations."The article provides recognition of customary sanctions against perpetrators of criminal acts. Article 601 paragraph (1) which states that, "Any person who commits an act that according to law living in society is declared a prohibited act shall be threatened with a crime. Based on this, it is clear that the meaning of criminal acts is not only limited to those stated according to laws and regulations, but also based on customary criminal law. The article provides recognition of customary sanctions against perpetrators of criminal acts. Article 601 paragraph (1) which states that, "Any person who commits an act that according to law living in society is declared a prohibited act shall be threatened with a crime. Based on this, it is clear that the meaning of criminal acts is not only limited to those stated according to laws and regulations, but also based on customary criminal law.The article provides recognition of customary sanctions against perpetrators criminal.